THE INFLUENCE OF SERVICE LEADERSHIP ON READINESS FOR CHANGE WITH ORGANIZATIONAL COMMUNICATION AS A MEDIATOR VARIABLE - Afdaliza, Afdaliza; Zamrul Aini (Ikatan Dosen Menulis, 2024)
Within the National Police institution, there are often changes in function and policy along with changes and rotation of leadership, which results in many policies changing, therefore it requires readiness to change members of the National Police so that they can maintain work performance. One important aspect in increasing the readiness to change members of the National Police is leadership style, especially servant leadership. Apart from that, there are variables that act as modifiers or interveners in the influence of service leadership on the readiness to change members of the National Police, especially the Police Non-Commissioned Officers of the Tangerang Police. This research aims to determine the influence of servant leadership on the readiness to change members of the National Police, Tangerang Police, and determine the influence of organizational communication as a modifying variable. The sampling method used is a purposive sampling technique. The primary data collection method was a questionnaire of 98 respondents. The analytical tool used is SEM (Structural Equation Model) using the SmartPLS version 3.0 program. The results of the research show that servant leadership has an influence on readiness to change, while the organizational communication variable shows a significant role as a mediator in the influence of servant leadership on the readiness to change of Tangerang Poresta police members.